2019
DOI: 10.1177/0963721419835214
|View full text |Cite
|
Sign up to set email alerts
|

Visible and Invisible Social Support: How, Why, and When

Abstract: Social relationships can be a vital source of help in difficult times. However, attempts to provide social support that is visible—direct and recognized by recipients as help—can sometimes have unintended negative effects. By contrast, invisible support—provided indirectly such that recipients do not interpret the behavior as help—can circumvent potential negative effects. In this article, we synthesize empirical evidence on support visibility using three organizing questions: How do support attempts differ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 34 publications
4
71
0
Order By: Relevance
“…For example, while a replication of the original invisible support study confirmed the costs of visible support, it did not find evidence for the expected benefits of invisible support (Shrout et al 2010). To address these inconsistencies, it has been recently proposed that the specific motivational needs of the support recipient may explain when visible vs invisible support can be beneficial (Zee and Bolger 2019). In particular, invisible support may be necessary when recipients are concerned about being evaluated (assessment motivation), while, when recipients want to take action (locomotion motivation) to overcome their current difficult situation, visible support may be required.…”
Section: Support Visibilitymentioning
confidence: 98%
See 2 more Smart Citations
“…For example, while a replication of the original invisible support study confirmed the costs of visible support, it did not find evidence for the expected benefits of invisible support (Shrout et al 2010). To address these inconsistencies, it has been recently proposed that the specific motivational needs of the support recipient may explain when visible vs invisible support can be beneficial (Zee and Bolger 2019). In particular, invisible support may be necessary when recipients are concerned about being evaluated (assessment motivation), while, when recipients want to take action (locomotion motivation) to overcome their current difficult situation, visible support may be required.…”
Section: Support Visibilitymentioning
confidence: 98%
“…Along this line, instances of support provided that are actually perceived by the recipient as help are referred to as visible support, while support that is provided indirectly and not perceived as such by the recipient is called invisible support (Bolger et al 2000). As compared to visible support, invisible support has been found to have positive effects on several individual and relational outcomes (see Zee and Bolger 2019). Invisible support, in fact, may not emphasize the recipient's difficulties or may help him/her to focus on adaptive stress and coping appraisals, without activating concerns about the equity of the support exchange.…”
Section: Support Visibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…RRT would suggest that it offers a social regulation resource and has less risk for difficult situations as they have been reported in the context of social support. In the literature, it could be shown that being the support receiver has downsides that might be explained with threats to autonomy and self-esteem (Bolger and Amarel, 2007; Maisel and Gable, 2009; Zee and Bolger, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other, receiving too much support might have negative consequences by making targets experience negative affect or feel indebted to agents, resulting in lower self-efficacy and reduced relationship satisfaction (e.g., Brock & Lawrence, 2009;Gleason et al, 2003). For this reason, some researchers have suggested that receiving more indirect forms of support may, under certain circumstances, yield better outcomes for targets (e.g., Bolger et al, 2000;Zee & Bolger, 2019). attitudes towards health-promoting behaviors, the self-efficacy to change their behaviors, and even the intentions to do so (Ferrini et al, 1994).…”
Section: Agent's Relational Beliefs → Agent's Relational Behaviors (B1)mentioning
confidence: 99%